Recall Value and Entry Word in Heading - Ranganathan, S. R. (Journal of Information and Knowledge, 2002)
This paper considers the rendering of the multiworded name of a Person, of an Organ of a Government, of an Institution, and of a Conference, and of the Title of a document in the Heading of a Catalogue Entry. The Canon of Prepotence taken along with the Principle of Probability is found sufficient to determine the Entry Word in a name-of-person. But, it is not so in the other cases. Nor is the Canon of Sought Heading of sufficient help in determining the Entry Word, though it is of help in determining the choice of heading for the Added Entries needed. The current practice of using the first word in the name of a corporate body or of the title of a document is of little Recall Value. It is suggested that the word of the greatest Recall Value should be made the Entry Word. In most cases, it happens to be the name of a subject or of some other speciality. To provide for this, the Canon of Recall Value is added to the list of the Normative Principles of Cataloguing.